Bioinspired intratumoral infusion port catheter improves local drug delivery in the liver - Federico Pedersoli; Imran Shair Mohammad; Anup Kumar Patel; Jonathan Kessler; Cherng Chao; Bo Liu; Chandana Lall; Catalina Guerra; John J. Park; F. Edward Boas (Scientific Reports)
Abstract Tumor immune modulation can be achieved using intratumoral injection of different immunomodulators during different phases of the cancer-immunity cycle. Intratumoral infusion catheters have been used in brain tumors, but these are not suitable outside the brain, where breathing motion results in catheter migration. Here, we use microstereolithography to manufacture a barbed sidehole catheter, modeled after the barbs in a bee stinger, where the barbs maintain the catheter position in the tumor, and sideholes within the barbs infuse drug into tumor tissue. In pig liver, we demonstrated 183-fold higher local drug concentration using the barbed sidehole catheter, compared to intravenous injection of water-soluble drug. High resistance sideholes and pulsatile injection both generate higher pressure in the catheter, which overcomes the tissue pressure, resulting in more drug delivery into tumor. A physical model of intratumoral infusion catheters accurately predicts the observed drug delivery results. Our catheter design is retained in the liver (and does not migrate out with breathing motion), and it preferentially infuses the drug into tumor tissue (not intratumoral vessels).